Festas, feiras, gambiarras e o fio de arame: expansões a partir do barroco latino-americano - Lopes, Maria Fernanda de Mello (2023)
This thesis develops the idea of cultural processes in relation to the notion of expansion. Its starting point is the idea of kludge (gambiarra), commonly understood as a creative popular solution. It leverages the term’s polysemy and its multifaceted potential to propose a flexible and expanding understanding, which will be used to highlight aspects of Latin American cultural processes. The reflection is structured around various creative scenarios identified in everyday practices such as fairs, festivities, street and public markets, artistic works, and innovation projects. This reveals a convergence in the presence of an inclusive logic that permeates them and tends to escape the logic of opposition guided patterns. The primary focus is on Latin American processes, incorporating a range of source materials, including bibliographic documents; journalistic pieces; photographs and video art. The research methodology is based on bibliographic and documentary sources. The central issue concerns how the construction of this idea of expansion can be useful for understanding cultural processes in Latin America. The hypothesis posits that the idea of expansion, explored through convergent examples and intertwined with theoretical reflections, offers a fertile approach for highlighting the dynamics of an inclusive logic within Latin American processes. The investigation centers on the field of communication and semiotics of culture. The theoretical framework draws on reflections about the Latin American baroque, in authors such as Severo Sarduy, Lezama Lima, Haroldo de Campos and Amálio Pinheiro, also incorporating the concept of bricolage, from Levis Strauss and Viveiros de Castro. The communicational understanding between cultural series in a complex society is informed by authors such as Iuri Lotman, Edgar Morin and Richard Sennet, among others. From the material collected, the study uncovers a convergence of ideas by linking examples of creative processes with theoretical reflections, forming the foundation for the idea of expansion. This idea encourages an understanding of the macro perspective through micro-level insights, fostering readings and practices that can go beyond dominant thinking. The thesis is divided into three chapters. The first chapter explores the idea of kludge (gambiarra) as a path towards an expansive perspective, using examples, mechanisms, characteristics, and their connections to the fields of art and innovation. The second chapter delves into the communication dynamics of street and public markets. The third chapter investigates the presence of the dynamics and characteristics discussed earlier in various environments and situations such as popular festivities. Despite their diversity, these scenarios are interconnected, thus pointing to practices and behaviors related to the order of expansion